1984
DOI: 10.1007/bf00165154
|View full text |Cite
|
Sign up to set email alerts
|

Combination radiofrequency hyperthermia and chemotherapy (BCNU) for brain malignancy

Abstract: Patients with high-grade primary and metastatic brain malignancies have a median survival time of 3-8 months, regardless of therapy. Because MagnetrodeTM hyperthermia provides safe, deep internal heating without normal-tissue injury, we studied its effects first on the brain and surrounding tissues of rabbits. The normal rabbit brain (n = 26) could be heated to potentially tumoricidal temperatures (42-43 degrees C) without apparent histopathologic or clinical damage to the brain, skull, external eye, subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In 1983, Britt et al [19] suggested the feasibility of ultrasonic hyperthermia for treating of malignant brain tumors. Tanaka et al [7] and Silberman et al [5] nearly at the same time, developed a method for local heating of brain tumor using radiofrequency waves of 13.56 MHz. However, the temperatures achieved in the tumor and brain were unpredictable, and bilateral bone flaps must be removed for the wave to penetrate into brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1983, Britt et al [19] suggested the feasibility of ultrasonic hyperthermia for treating of malignant brain tumors. Tanaka et al [7] and Silberman et al [5] nearly at the same time, developed a method for local heating of brain tumor using radiofrequency waves of 13.56 MHz. However, the temperatures achieved in the tumor and brain were unpredictable, and bilateral bone flaps must be removed for the wave to penetrate into brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Two methods are currently used to induce hyperthermia of brain tumor: 1) Capacitive heating using RF wave with a frequency of 13.57MHz [5,7]. Because of the attenuation of energy by bone, portions of skull must be removed bilaterally.…”
Section: Al [31mentioning
confidence: 99%
See 1 more Smart Citation
“…10 was also entered in a radiofrequency hyperthermia treatment program [99,100]. Using implanted probes, it is possible to reach tumoricidal temperatures of 42 ° C to 43 ° C in tumors without damage to adjacent struc- Fig.…”
Section: Protein Synthesismentioning
confidence: 99%
“…Moderate hyperthermia is a potential adjuvant treatment for conventional chemoradiation therapy. Various methods of moderate hyperthermia have been described, including dielectric warming with microwaves 4,15) or radiowaves 11,16) and magnetic induction implant heating. 10) The theory is based on inhibition of ribonucleic acid and/or deoxyribonucleic acid synthesis in proliferating cells in the S and early G 2 phases.…”
Section: Introductionmentioning
confidence: 99%